THE INFLUENCE OF PUBLIC SERVICE QUALITY AND IMPACT ON PUBLIC SATISFACTION AT THE PANYALAIAN VILLAGE OFFICE - Nasfi Nasfi; Ningsih Yulia; Oktaviane Diga Putri (Jurnal Apresiasi Ekonomi, 2026)
The Nagari or Village Office is the lowest Government Agency in providing public services to village communities, expected to be able to create community satisfaction, in fact public services are not yet optimal. The purpose of this study was to determine the effect of reliability, responsiveness, physical ability, assurance, and attention on community satisfaction from the services of the Panyalaian Village Office. Quantitative research method, the object of the Panyalaian Village Office research used a questionnaire filled out by related parties of Panyalaian Village, a population of 503 people and to determine the sample used the Slovin formula with a tolerance level of 5% and obtained a sample of 144 respondents, data analysis techniques statistical analysis SPSS version 30.2024. The results showed that there was a partial significant effect between reliability on community satisfaction of 12.1% and attention to the community of 11.7%, and there was no partial significant effect between responsiveness on community satisfaction of 0.04%, physical ability on community satisfaction of 0.07%, and assurance on community satisfaction of 0.01%. There was a simultaneous influence of the five independent variables on community satisfaction of 11.0%. Keywords: Reliability, Responsiveness, Physical Capability, Assurance, Attention and Customer Satisfaction